High strength Hadfield steel produced using laser powder bed fusion of mixed powders - Cheng, Baisong (2023)
Hadfield steel (HS) containing ∼0.83 wt% Carbon has been manufactured using the laser powder bed fusion (LPBF) of mixed Fe-Mn, pure-Fe and Fe-C powders. Results show that the as-fabricated alloy is fully austenitic with the absence of carbides—a typical feature in the cast alloy that necessitates its solutionizing and quenching. The strength (σy = 595.5 ± 18.1 MPa, σu = 950.2 ± 28.6 MPa) and hardness (318.6 ± 7.1 HV) of the LPBF HS are superior to those of the conventionally fabricated HS, while the impact toughness is similar, and ductility is inferior. The yield strength enhancement is mainly due to the refinement in the grain size and increase in the dislocation density, which occurs due to the rapid solidification conditions that prevail during LPBF. This rapid solidification also prevents carbide formation and retain the main alloying elements (C and Mn) in solution. Thus conventional water quenching process can be completely eliminated.